Factor Analysis of Female Leadership on Quality of Public Madrasah Ibtidaiyah - Julizar, Najma; Manumanoso Prasetyo, Muhammad Anggung; Zulmaulida, Rahmy (Journal Of Education And Teaching Learning (JETL), 2024)
The study aims to determine the significant influence of leadership policies, innovation and communication skills on the quality of madrasah; The study used quantitative research methods using path analysis techniques. The study population amounted to 158 teachers from 8 public madrasah ibtidaiyah in Pidie Jaya district. Sample determination using purposive sampling with the Slovin formula. The results showed that: The innovation of the madrasah principal does not have a significant effect on the quality of madrasah with a P-Value of 0.075 > 0.05, while the leadership policy obtained a P-Value of 0.050 ? 0.05 and communication skills P-Value of 0.036 < 0.05, where there is a significant effect on the quality of madrasah. Identification of other factors that are thought to have an impact on the quality of madrasah include madrasah culture, professionalism, facilities and infrastructure. These variables are recommended to be researched. The social implications of the research results explain that there is no gender dichotomy in the concept of quality madrasah.